Fake news das eleições de 2018: entre a cultura isolada e a influência eleitoral - Vasconcelos, Fredimir Alex (2021)
The massification of social networks became an important variable in electoral processes, relevant to studies and reflections: the spread of false content through new media, fake news. In Brazil, this issue became strong in the 2018 presidential election campaign. So this paper seeks to analyze the historical, political, economic, social, linguistic and technological contexts which allowed the spread of fake news as part of the constitution national process. The characteristics of Brazil that appears in fake news is what it is expected to bring up. The study justify itself by mobilize cultural and linguistic aspects inserted in a reality of technological tools capable of effecting individualized communication on a large scale. Among the points surveyed, are the content and language of the messages, mainly those that aimed to reaffirm prejudices regarding the social conquests of movements and organized civil society during the third millennium, identity guidelines and religious issues. So, “isolated” here is the portion of the population that, while maintaining characteristics of the “popular”, by Barbero (1997), shows as conservative aspects and strong influence of the mass sensationalist media, but diverges from the “popular” defended in works related to social movements and other social demand groups. The analysis is related to the construction of networks to reach millions of voters and distribute messages, mainly through the WhatsApp application, in the cyberculture times. It is expected to collaborate in the understanding of the phenomenon and to propose questions for deeper studies of the phenomenon in Language Studies.